Thanatephorus target spot on rubber tree in the Amazon: Phylogenetics and genetic variation in populations of the Pathogen - Basseto, Marco Antonio; Vicentini, Samara Nunes Campos [UNESP]; Gasparotto, Luadir; Ceresini, Paulo Cezar (FapUNIFESP (SciELO), 2019)
Thanatephorus target spot is one of the most important diseases of rubber tree (Hevea brasiliensis) in the Amazon. However, an important question about the actual phylogenetic placement of this pathogen has not been answered yet. In this study, we analyzed the patterns of genetic variation in sequences of the ITS-5.8S rDNA region from a population of T. cucumeris (asexual phase = Rhizoctonia solani AG 2-2) associated with the rubber tree target spot sampled in Belém (Pará), Manaus (Amazonas) and Xapuri/Rio Branco (Acre), phylogenetically comparing with worldwide described members of AG 2. This study represents an important step to reveal the etiology of the asexual phase of T. cucumeris in the rubber tree. Phylogenetically, based on Bayesian analyses, we found support to nominate a new group of R. solani anastomosis associated with rubber tree target spot: AG 2-2 Hb. This group consisted of an independent evolutionary unit in relation to the worldwide described sub-groups of AG 2-2. Considering the gene genealogy built by coalescent analysis, we observed that the population of R. solani AG 2-2 Hb from Belém was relatively older than the other two analyzed populations. The common ancestor of all three populations is associated with passion-fruit (Passiflora edulis) foliar blight in Belém and has about 0.8 coalescent evolutionary units of age. No haplotype of the ITS-5.8S region of AG 2-2 Hb from Belém was observed in any other region. However, the population from Manaus shared two of its four haplotypes with those observed in Xapuri/Rio Branco, Acre, indicating gene flow.
Mancha areolada de Thanatephorus da seringueira na Amazônia: Identificação filogenética e variação genética em populações do patógeno
Keywords: Anastomosis groups; Rhizoctonia solani; Ribosomal DNA; Thanatephorus cucumeris